Management of oncohematological neoplasms in the COVID-19 pandemic: experts recommendation - Alcarraz, Cindy (2021)
The ongoing COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a global public health crisis. Many reports indicate disappointing results in cancer patients compared to the general population. Therefore, experts in the management of oncohematological malignancies from the National Institute of Neoplastic Diseases, national hospitals and a private clinic in Metropolitan Lima have developed recommendations obtained by consensus to continue with the management of patients with oncohematological neoplasms safely in the face of the pandemic.